Exploring the Impact of Affective Relationship Quality, Independence, and Support on Perceptions of Parental Favoritism Among Siblings - Sonila Ali; Ibrahim Shah (PT FORMOSA CENDEKIA GLOBAL, 2023)
To examine the perceptions of Parental Favoritism on Gender, Birth Order and Self and other siblings on three variables: Affective Quality Relationship, Independence, and Support. The data utilized in the analysis were obtained from a sample of 141 people (76 males and 65 females) from Karachi. Participants were assessed by Parental Favoritism Questionnaire and Parental Attachment Questionnaire (PAQ). The PAQ consists of three scales. The study examines the interplay between affective quality, relationship independence, and support.. The three hypotheses were: 1. perceived parental favoritism will be high in self and other siblings as compared to self only and others sibling only 2. Females will get more favored by parents as compared to males 3. First and last-born children will be more favored by parents than middle born. By applying one way ANOVA and Independence T-Test, the findings indicated statistically significant that perceived parental favoritism was high in self and other siblings as compared to self only and other siblings only in terms of affective quality relationship and independence. The findings also revealed that parents preferred females over males more in establishing effective quality relationships and providing support.